The effect of an exopolysaccharide probiotic molecule from Bacillus subtilis on breast cancer cells - Nguyen, Mai R.; Ma, Emily; Wyatt, Debra; Knight, Katherine L.; Osipo, Clodia (Frontiers in Oncology, 2023)
Many well-known risk factors for breast cancer are associated with dysbiosis (an aberrant microbiome).However, how bacterial products modulate cancer are poorly understood. In this study, we investigated the effect of an exopolysaccharide (EPS) produced by the commensal bacterium Bacillus subtilis on breast cancer phenotypes. Although B. subtilis is commonly included in probiotic preparations and its EPS protects against inflammatory diseases, it was virtually unknown whether B. subtilis-derived EPS affects cancer. This work investigated effects of EPS on breast cancer cells as a cancer model. Shortterm treatment with EPS inhibited proliferation of certain breast cancer cells (T47D, MDA-MB-468, HCC1428, MDA-MB-453) while having little effect on others (MCF-7, MDA-MB-231, BT549, ZR-75-30).EPS induced G1/G0 cell cycle arrest of T47D cells while increasing apoptosis of MDA-MB-468 cells.EPS also enhanced aggressive phenotypes in T47D cells including cell migration and cancer stem cell survival. Long-term treatment with EPS (months) led to resistance in vitro and promoted tumor growth in immunocompromised mice. RNA-sequence analysis showed that EPS increased expression of proinflammatory pathways including STAT1 and NF-B. IKK and/or STAT1 signaling was necessary for EPS to modulate phenotypes of EPS sensitive breast cancer cells. These results demonstrate a multifaceted role for an EPS molecule secreted by the probiotic bacterium B. subtilis on breast cancer cell phenotypes. These results warrant future studies in immune competent mice and different cancer models to fully understand potential benefits and/or side effects of long term use of probiotics.